Pyrosequencing Analysis of Bacterial Diversity in 14 Wastewater Treatment Systems in China - Wang, Xiaohui (American Society for Microbiology, 2012)
To determine if there is a core microbial community in the microbial populations of different wastewater treatment plants (WWTPs) and to investigate the effects of wastewater characteristics, operational parameters, and geographic locations on microbial communities, activated sludge samples were collected from 14 wastewater treatment systems located in 4 cities in China. High-throughput pyrosequencing was used to examine the 16S rRNA genes of bacteria in the wastewater treatment systems. Our results showed that there were 60 genera of bacterial populations commonly shared by all 14 samples, including Ferruginibacter, Prosthecobacter, Zoogloea, Subdivision 3 genera incertae sedis, Gp4, Gp6, etc., indicating that there is a core microbial community in the microbial populations of WWTPs at different geographic locations. The canonical correspondence analysis (CCA) results showed that the bacterial community variance correlated most strongly with water temperature, conductivity, pH, and dissolved oxygen (DO) content. Variance partitioning analyses suggested that wastewater characteristics had the greatest contribution to the bacterial community variance, explaining 25.7% of the variance of bacterial communities independently, followed by operational parameters (23.9%) and geographic location (14.7%). Results of this study provided insights into the bacterial community structure and diversity in geographically distributed WWTPs and discerned the relationships between bacterial community and environmental variables in WWTPs.